Consumer protection and the criminal law : law, theory, and policy in the UK - Cartwright, Peter (Cambridge University Press, 2001)
How does criminal law affect consumers? Cartwright considers issues of consumer protection, asking whether the state should intervene between consumers and producers. He considers topics including trade descriptions and product safety, and considers how far UK law should hold traders (particularly corporations) to account for their activities towards consumers.